Cognitive control and unusual decisions about beauty: an fMRI study - Flexas, Albert; Rosselló, Jaume; de Miguel, Pedro; Nadal, Marcos; Munar, Enric (Frontiers in Human Neuroscience, 2014)
Studies of visual aesthetic preference have shown that people without art training generally prefer representational paintings to abstract paintings. This, however, is not always the case: preferences can sometimes go against this usual tendency. We aimed to explore this issue, investigating the relationship between ‘unusual responses’ and reaction time in an aesthetic appreciation task. Results of a behavioural experiment confirmed the trend for laypeople to consider as beautiful mostly representational stimuli and as not beautiful mostly abstract ones (‘usual response’). Furthermore, when participants gave unusual responses, they needed longer time, especially when considering abstract stimuli as beautiful. We interpreted this longer time as greater involvement of the cognitive mastering and evaluation stages during the unusual responses. Results of an fMRI experiment indicated that the anterior cingulate, orbitofrontal cortex and insula were the main structures involved in this effect. We discuss the possible role of these areas in an aesthetic appreciation task.